IDENTIFIKASI KARAKTERISTIK WISATAWAN DI KAWASAN PANTAI LAMPUUK - Khairunsurya Khairunsurya; Izziah Izziah; Yusria Darma (Prodi Magister Teknik Sipil Unsyiah, 2019)
Lampuuk Beach is the most visited beach by both local and foreign tourists. Based on data from the Aceh Besar Culture and Tourism Office (2018) that in 2017 the number of local and foreign tourists reached 1,075,626 people with a growth of 4.75%, the number was the highest compared to tourist visits to other tourist objects in Aceh Besar. To develop beach tourism activities and increase tourism interest in Lampuuk Beach in Aceh Besar District, it is necessary to conduct research related to the arrangement of coastal areas by improving the environmental quality of coastal areas. The purpose of this study is to identify the characteristics of tourists in the area Lampuuk Beach. The benefits of this research as input for local government and local communities for policy formulation in the development of tourist area, arrange Lampuuk Coast resort management structuring by reviewing current condition and alternative arrangement in the future. The method used in this research is mixed methods between quantitative method and qualitative method, and analysis used is contant analysis). The result of analysis shows identification of tourist characteristic in Lampuuk Coast area is is nusantara tourist equal to 99,42%, tourist gender 86,6% are male, age group often visit with age 25-55 year equal to 47%, education last tourist D3 by 41,86%, work type of worker working equal to 63,92%, tourist expenditure during the beach between Rp. 100,000-Rp. 200.000 is 44,93%, tourist visit destination is 100% travel, visit frequency every year equal to 40,56%, friend of traveler visit trip is with friend equal to 37,11%, stay length of traveler greater than 5 hour at beach 72, 16%, the residence of the majority tourists with no stay of 79.38%, the type of expenditure of tourists for the tickets, the cost of parking, and consumption during the beach, the transportation used by tourists 50.52% by using motorcycles, the motivation of tourists visited Lampuuk Beach because the natural beauty of 45.36%, the source of information to visit tourists get from friends and family, the activities undertaken in Lampuuk Beach is to enjoy the beauty of nature and bathing, the willingness of tourists to return 100% return.